The Embryological Interpretation of Gen 2:7 and its Use in Dyophysite Christology - Tilley, Nathan (2024)
This article traces the rise of the embryological interpretation of Gen 2:7 and how it came to provide arguments for dyophysite Christology. By the late 4th century, many Christian writers saw in the formation of Adam a depiction of the formation and ensoulment of a human embryo. Moreover, authors around the 5th century connected the embryological reading of Adam’s formation with the life of Christ in the womb. But in the 6th and 7th centuries, this interpretation of Gen 2:7 became controversial. Debates about Christ raised the stakes of disagreement over the time of human ensoulment, and embryological readings of Adam’s creation were caught up in these debates. In this context, East Syrian Babai the Great (551-628) deployed the embryological reading of Gen 2:7 against Christological rivals in defense of his theory of Christ’s delayed ensoulment in the womb. In doing so, he offers a biological account of Christ’s pre-ensouled life as a plant and zoophyte. But the connection between an embryological reading of Gen 2:7 and dyophysite Christology also prompted opponents to turn to exegetical strategies that excluded any analogy with delayed ensoulment. This article thus presents an example of how theological controversy and the history of science affected biblical exegesis.
Keywords: Babai the Great; Christology; Gen 2:7; Biblical Exegesis; Embryology; ensoulment